ASSESSMENT OF PHYSICOCHEMICAL PARAMETERS AND OCCURRENCE OF ANTIBIOTICS IN LIVESTOCK WASTEWATER IN RAWALPINDI PAKISTAN - Tahira Yasmin; Asma Jabeen; Shazia Iram (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Wastewater from livestock farms can contain high levels of organic matter and emerging pollutants, including antibiotics, which pose potential risks to environmental and public health. Seasonal variations can influence the physicochemical properties and presence of pollutants in wastewater. Objectives: The study aimed to analyze the physicochemical parameters of wastewater samples from livestock farms in Rawalpindi, Pakistan, across summer and winter seasons and to detect the presence of seven common antibiotics to assess the pollution level and potential impact on receiving water bodies. Methods: Sixty wastewater samples were collected from livestock farms of various sizes in both summer and winter seasons. Standard methods were used to measure physicochemical parameters, including temperature, pH, total dissolved solids (TDS), electrical conductivity (EC), biological oxygen demand (BOD), chemical oxygen demand (COD), total Kjeldahl nitrogen (TKN), and total phosphorus (TP). Antibiotics were detected using reverse-phase high-performance liquid chromatography (HPLC) after sample preparation by the QuEChERS method, targeting ampicillin (AMP), amoxicillin (AMO), oxytetracycline (OTC), sulfamethazine (SMZ), sulfadiazine (SDZ), enrofloxacin (ENR), and trimethoprim (TMP). Results: High BOD and COD values indicated significant organic matter content. pH levels were generally within WHO permissible limits, with only four samples exceeding pH 9 (beyond NEQS limits). A paired t-test revealed seasonal variations: temperature, TDS, and EC were higher in summer, while pH, BOD, COD, TKN, and TP were elevated in winter. The BOD/COD ratio indicated that most samples were biodegradable, with values over 0.5. Antibiotics were detected in 40% of summer and 26.66% of winter samples, with no antibiotics found in 43.33% of summer and 45% of winter samples. Most antibiotics detected were from the sulfonamide class, followed by ampicillin and tetracycline. Trimethoprim was the least detected, while enrofloxacin was only detected in winter (8.33%), possibly due to photolysis. Conclusions: Livestock farms in Rawalpindi contribute pollutants, including antibiotics, to surrounding water bodies, presenting risks to environmental and public health. The seasonal differences in pollutants suggest a need for year-round monitoring and improved wastewater management